PENEMUAN MUHAMMAD BIN MUSA AL KHAWARIZMI - Aldewo Dillon Perkasa; Mohammad Luthfan Faohan; Kania Dewi; Galuh Inti Aulia; Hisny Fajrusallam (Jurnal Soshum Insentif, 2021)
Abstract - This study aims to examine the findings of an Islamic scientist named Al Khwarizmi or better known as "Al Jabar", about the implementation and development of his mindset towards technological life today. And Islam gave birth to many figures and scientists who gave great influence and contribution to every development of science. Including Al-Khwarizmi as a scientist who is known in the field of mathematics. And work in other worlds of science. Education also proves that expertise is not only in the field of sharia but in the fields of philosophy, logic, arithmetic, music, Islamic history and chemistry. By giving his contribution Alkawarizmi caused the civilized phase until now in the developed world because of the results of his research. And he has earned the caliph's trust, until research says Alkhwarizmi is the "Father of Al-Jabar" in the world of this monumental science Abstrak - Penelitian ini bertujuan untuk menelaah penemuan – penemuan dari seorang ilmuan Islam yang bernama Al Khawarizmi atau lebih dikenal sebagai “Al Jabar”, tentang implementasi dan perkembangan pola pikirnya terhadap kehidupan berteknologi pada masa sekarang. Dan Islam melahirkan banyak tokoh-tokoh serta ilmuwan yang memberi pengaruh dan kontribusi besar setiap perkembangan ilmu pengetahuan. Termasuk Al-Khawarizmi sebagai ilmuwan yang dikenal dibidang matematika. Dan berkarya dalam dunia ilmu pengetahuan yang lain. Pendidikan juga membuktikan bahwasanya Keahlian bukan sekedar bidang syari`at saja akan tetapi dalam bidang filsafah, logikam, aritmatika musik, Sejarah Islam dan kimia. dengan memberikan kontribusinya Alkawarizmi menyebabkan fase beradapan hingga sampai sekarang didunia yang maju karena hasil penelitiannya. Dan beliau telah mendapatkan kepercayaan Khalifah, Hingga riset mengatakan Alkhawarizmi ini sebagai “Bapak Al-Jabar” di dunia ilmu pengetahuan yang fonumental tersebut.